The host cell factor DDX3 mediates sex dimorphism in the IFNα response of plasmacytoid dendritic cells upon TLR activation - Sebastian Schloer; Jana Hennesen; Lena Rueschpler; Mohamed Zamzamy; Felix Flomm; Wing Hang Ip; Andrea Pirosu; Thomas Dobner; Marcus Altfeld (Pharmacological Research)
During the course of viral infections, IFN-I producing pDCs are fundamental in establishing antiviral defense. However, little is known about the molecular mechanisms by which biological sex contributes to differences in IFN-I production by pDCs. Here, we aimed to identify X-chromosome-encoded proteins as a source of sex differences in IFN-I responses by pDCs. We identified the host-cell factor DDX3 as a key mediator for the sex dimorphism in the IFNα response. DDX3 was significantly higher expressed in female pDCs and was translocated together with IRF7 to the nucleus to orchestrate IFN-I transcription. DDX3 as driver of sex differences in the initial and chronic IFN-I response might serve as a novel target to limit IFN-I-mediated hyperactivation of immune cells.